2013
DOI: 10.1038/modpathol.2013.73
|View full text |Cite
|
Sign up to set email alerts
|

ALK-positive large B-cell lymphomas express a terminal B-cell differentiation program and activated STAT3 but lack MYC rearrangements

Abstract: ALK-positive large B-cell lymphoma is an aggressive lymphoid neoplasm characterized by a monomorphic proliferation of immunoblast-like cells expressing a plasmablastic phenotype and carrying ALK rearrangements. MYC rearrangements are frequent in plasmablastic lymphomas, advanced plasma cell myelomas and a subgroup of diffuse large B-cell lymphomas, but their presence in ALK-positive large B-cell lymphomas is unknown. MYC expression is downregulated by BLIMP1, a master modulator of plasma cell differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…One research indicated that ALK-positive large B-cell lymphomas express a complete plasmablastic differentiation program but, contrary to plasmablastic lymphomas, do not have MYC rearrangements [30]. It was consistent with the low MYC expression level in our study, which suggested that MYC may not be the main molecular pathogenesis for the highly aggressive nature of ALK+, LBCL.…”
Section: Discussionsupporting
confidence: 89%
“…One research indicated that ALK-positive large B-cell lymphomas express a complete plasmablastic differentiation program but, contrary to plasmablastic lymphomas, do not have MYC rearrangements [30]. It was consistent with the low MYC expression level in our study, which suggested that MYC may not be the main molecular pathogenesis for the highly aggressive nature of ALK+, LBCL.…”
Section: Discussionsupporting
confidence: 89%
“…68,69 STAT3 upregulation mediated by activated ALK is considered to contribute to the upregulation of MYC in these tumors. 69 Primary mediastinal large B-cell lymphoma is a distinctive entity showing a localized mediastinal mass as a principal clinical finding. 7 Genetic abnormalities of MYC are not common in this lymphoma.…”
Section: Myc Activation In Other Aggressive Large B-cell Lymphomamentioning
confidence: 99%
“…Contrary to other PBL types, these tumors do not carry MYC translocations, but express high levels of MYC protein. 90 The mechanism activating MYC in these tumors is not clear, but may be a consequence of STAT3 activation. STAT3 is a downstream effector of ALK and is phosphorylated in ALK-positive LBCL.…”
Section: Dh/th Lymphomamentioning
confidence: 99%